Social Entrepreneurship Development Trends in the Tourism Industry - TUYAKOVA, Aiman; BEISENGALIYEV, Berik; BURLAKOV, Leonid; SAIMAGAMBETOVA, Gaukhar; TUREKULOVA, Assiya (Journal of Environmental Management and Tourism, 2021)
Global challenges and threats, which inevitably affect the entire world community, naturally enhance the interdependence of states; require their joint actions aimed at solving social and economic problems of the world economy. As a result, the influence on the formation of the national social policy of the Re, both global social risks and global trends in the organization and financing of the social sphere, increases. The analysis of the study consists of a review of the current literature on social tourism, including a descriptive analysis of the literature undertaken to assess the theoretical foundations and connections in order to analyze the contribution of social tourism to the economy. This study identifies avenues for further research in the field of social tourism, which can serve as a basis for a post-image restructuring of the global tourism industry.